2022
DOI: 10.1186/s12985-022-01813-2
|View full text |Cite
|
Sign up to set email alerts
|

NSAID use and clinical outcomes in COVID-19 patients: a 38-center retrospective cohort study

Abstract: Background Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to reduce pain, fever, and inflammation but have been associated with complications in community-acquired pneumonia. Observations shortly after the start of the COVID-19 pandemic in 2020 suggested that ibuprofen was associated with an increased risk of adverse events in COVID-19 patients, but subsequent observational studies failed to demonstrate increased risk and in one case showed reduced risk associated with NSAID u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
(34 reference statements)
0
16
0
Order By: Relevance
“…Other studies, including a systematic review and meta‐analysis by Zhou et al., 7 and a retrospective study by Reese et al., 57 confirmed the safety of NSAIDs in COVID‐19.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies, including a systematic review and meta‐analysis by Zhou et al., 7 and a retrospective study by Reese et al., 57 confirmed the safety of NSAIDs in COVID‐19.…”
Section: Discussionmentioning
confidence: 86%
“…103,104 A study by the EU Pharmacovigilance Risk Assessment Committee reported that ibuprofen, at a dose up to 1200 mg/day, is not associated with any cardiovascular risk. 105 Other studies, including a systematic review and meta-analysis by Zhou et al, 7 and a retrospective study by Reese et al, 57 confirmed the safety of NSAIDs in COVID-19.…”
Section: Discussionmentioning
confidence: 93%
“…ibuprofen, flurbiprofen, etoricoxib or paracetamol, had no effects on ACE2 expression or activity in vitro or in vivo (de Bruin et al, 2022). A human study also observed that NSAID use was not associated with increased COVID-19 severity (Reese et al, 2022). However, the effects of NSAIDs for managing post-COVID pain have not been investigated yet.…”
Section: Covid Painmentioning
confidence: 99%
“…Differences in COX‐independent mechanisms among these compounds have already been described (Tegeder et al, 2001 ). Because additional effects may affect either efficacy or toxicity, these may have therapeutic consequences depending on a specific disease and/or patient, possibly accounting for weak associations between NSAID use and COVID‐19 protection (Reese et al, 2022 ; Zhou et al, 2022 ). Therefore, the underlying mechanism(s) leading to different COVID‐19 outcomes depending on the NSAID used should be elucidated.…”
Section: Introductionmentioning
confidence: 99%